Moebius Syndrome and Depressor Anguli Oris Muscle Hypoplasia - Borges, Joana (2021)
Neonatal asymmetric crying facies is often underrecognized and is usually caused by hypoplasia/agenesia of the depressor angular oris muscle of the lip. This condition leads to newborn facial asymmetry of the mouth and lips while crying or smiling, being other functions of the facial muscles, such as frowning, eye closure, and nasolabial fold depth, normal. It differs from complete facial palsy, which can occur isolated or as part of a syndrome, such as Moebius Syndrome. Moebius Syndrome is a rare disease characterized by non-progressive congenital palsy of the facial (VII) cranial nerve. Other cranial nerves involvement, mostly the external ocular motor (VI) nerve, is frequent. We present the case of a female preterm infant, born through an uncomplicated vaginal delivery. Prenatal screening tests were normal. Feeding difficulty was noted in the first hour of life. Physical examination showed generalized facial hypomimia, asymmetric face on crying (right and downwards deviation of the mouth angle) and absence of external ocular movements. Clinical diagnoses of Moebius Syndrome together with left depressor angular oris muscle hypoplasia were hypothesized. Magnetic resonance imaging showed bilateral absence of the VII cranial nerve and left VI cranial nerve, compatible with the diagnostic hypothesis. Multidisciplinary follow-up and early intervention is extremely important to alleviate MS consequences, particularly language and communication impairments.